Organizational Behavior Factors in the Implementation of Regional Financial Accounting Systems - Musa, Chalid Imran (PT. Maju Malaqbi Makkarana, 2024)
Implementation of financial accounting systems is a complex process involving various factors, including organizational behavior. Organizational behavior factors play an important role in determining the success or failure of system implementation. This abstract discusses the background of the problem regarding organizational behavior factors in the implementation of financial accounting systems. Problems that often arise related to organizational behavior factors in the implementation of financial accounting systems include resistance to change, lack of management support, lack of skills and knowledge, lack of communication and involvement, and an organizational culture that does not support change. Resistance to change can arise from discomfort with changes in usual work routines or uncertainty about the success of the new system. Inadequate management support can hinder employee participation and motivation in adopting the new system. Lack of skills and knowledge needed to operate the new system can hinder effective acceptance and use. Ineffective communication and lack of employee involvement in the implementation process can lead to ambiguity and resistance. An organizational culture that does not support change and innovation can be a serious obstacle to the implementation of financial accounting systems. In addressing organizational behavior factors, it is important to pay attention to employee attitudes and perceptions, management support, effective communication, training and learning, and an organizational culture that supports change. Involving employees in the planning and decision-making stages, providing adequate training, and creating a culture that is open to change can increase the success of implementing a financial accounting system.